Identification of Junior High School Students' Mathematical Problem Solving Abilities on Number Patterns - Parindang, Edwin Amanu; Ramlan, Wahyudi; Wahyuni, Reni; Salman , Muhammad (EDUPEDIA Publisher, 2025)
This study aims to analyse the mathematical problem-solving abilities of middle school students in the context of number patterns. Using a descriptive qualitative method, the research was conducted on eighth-grade students at SMP Negeri 3 Tualang. The instruments used included problem-solving tests in the form of essay questions and interviews. Subjects were selected using purposive sampling, consisting of 6 students with varying abilities (high, medium, low). The results show that students have varying abilities in four problem-solving indicators: understanding the problem (50% - medium), planning the solution (8.33% - very low), solving the problem (100% - very high), and reviewing the solution (25% - low). The data indicates that while students are capable of solving problems and understanding the questions, they struggle with planning solutions and reviewing their answers. It is recommended to enhance teaching strategies with more flexible approaches, such as problem-based learning (PBL), to improve students' mathematical problem-solving skills.